Integrating SLAM and gas distribution mapping (SLAM-GDM) for real-time gas source localization. (2nd September 2018) - Kamarudin, Kamarulzaman; Md Shakaff, Ali Yeon; Bennetts, Victor Hernandez; Mamduh, Syed Muhammad; Zakaria, Ammar; Visvanathan, Retnam; Ali Yeon, Ahmad Shakaff; Kamarudin, Latifah Munirah
ABSTRACT: Gas distribution mapping (GDM) learns models of the spatial distribution of gas concentrations across 2D/3D environments, among others, for the purpose of localizing gas sources. GDM requires run-time robot positioning in order to associate measurements with locations in a global coordinate frame. Most approaches assume that the robot has perfect knowledge about its position, which does not necessarily hold in realistic scenarios. We argue that the simultaneous localization and mapping (SLAM) algorithm should be used together with GDM to allow operation in an unknown environment. This paper proposes an SLAM-GDM approach that combines Hector SLAM and Kernel DM + V through a map merging technique. We argue that Hector SLAM is suitable for the SLAM-GDM approach since it does not perform loop closure or global corrections, which in turn would require to re-compute the gas distribution map. Real-time experiments were conducted in an environment with single and multiple gas sources. The results showed that the predictions of gas source location in all trials were often correct to around 0.5–1.5 m for the large indoor area being tested. The results also verified that the proposed SLAM-GDM approach and the designed system were able to achieve real-time operation. GRAPHICAL ABSTRACT: